IMPLEMENTING OUTCOME-BASED EDUCATION: ENSURING ALIGNMENT WITH PROGRAM OUTCOMES IN INDONESIAN ENGLISH LANGUAGE TEACHING - Aswadi Jaya; Kurnia Saputri; Darmawan Budiyanto; Nur Fathiyya Zahira Mujahidah (University of Kuningan, 2025)
This study investigates the implementation of Outcome-Based Education (OBE) in Indonesian higher education, focusing on how English language programs ensure alignment between Program Outcomes (POs) and Program-Specific Outcomes (PSOs). Using a qualitative descriptive approach, the research synthesizes insights from curriculum frameworks, institutional policy documents, and prior empirical studies on OBE-based English language instruction. The analysis demonstrates that effective OBE implementation fosters not only students’ linguistic accuracy and fluency but also their critical reading, academic writing, and collaborative problem-solving abilities. Moreover, OBE promotes the integration of socio-cultural awareness, ethical communication, and digital competence as essential dimensions of communicative proficiency. Pedagogical innovations such as project-based learning, authentic performance assessment, and the use of digital learning environments like Google Classroom and AI-supported writing tools enable measurable learning outcomes aligned with 21st-century competencies. Nonetheless, the study identifies ongoing challenges, including limited teacher readiness, uneven institutional commitment, and misalignment between assessment instruments and higher-order learning objectives. Conceptually, this research positions OBE as a transformative educational model that shifts English language teaching in Indonesia from content transmission to outcome-oriented learning. It further emphasizes the importance of continuous curriculum review and systematic professional development to sustain its successful implementation. The findings provide both theoretical reinforcement for constructive alignment in curriculum design and practical guidance for English language educators in advancing quality assurance within higher education.